WAX DEPOSITION BEHAVIOR IN ETHYLENETETRAFLUOROETHYLENE COATED PIPE AS COMPARED TO PVC AND STEEL PIPES AT DYNAMIC AND STATIC CONDITIONS. - BAGDAT, MOMBEKOV (2015)
The deposition of wax on the inner surface of subsea pipelines is a prevalent problem during the production and transportation of waxy crude oil. It can reduce effective diameter and restrict fluid flow through the pipeline. The present study evaluates the effect of Steel pipe, Polyvinyl Chloride (PVC) pipe and Ethylene- TetraFluoroEthylene (ETFE) coated pipe on wax deposition at different temperatures and flow rates. A flow loop facility was designed to investigate the effect of different pipe surfaces on wax deposition or inhibition. Increasing temperature differential between crude oil and pipe wall generally increased the deposition in the three pipes. However, the amount of wax content gradually reduces as deposition thickness increases due to increasing trapped oil within the deposits. Conversely, as flow rate increases, the deposition thickness reduces, indicating less trapping of the oil as the concentration of the deposited wax increases.